Consumer Behaviour towards Two Wheelers and Four Wheelers: A Study on Rural and Urban Mizoram - Laldinliana (Indian Journal of Marketing, 2012)
Vehicles are identified as a means of logistic and conveyance, a dynamic of livelihood, and even an insignia of wealth and luxury. Whatever the perception be, vehicles, whether two-wheelers or four-wheelers, are expensive and need constant care and maintenance. This paper tries to study the factors considered in buying two-wheelers and four-wheelers in Mizoram, a remote and rugged State in the North East corner of India having a total road length of 4,046.37 kms, out of which 2,220.30 kms were surfaced road (Census of India, 2001) and only 18 petrol pumps all over the State (Economic and Statistics, 2008). Given the various infrastructural constraints and backwardness of the State, the present study tries to identify which of the ancillary attributes play prominence in the buying behaviour of the rural and urban Mizoram consumers with respect to two-wheelers and four-wheelers.